Manajemen Mutu Pendidikan pada Tingkat Dasar dan Menengah - Faizal Djabidi (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2017)
Education is essentially a process of maturation of quality of life. Through this process, it is expected that humans can understand what the meaning and nature of life are as well as for what and how to carry out the tasks of life and life correctly. That's why the focus of education is directed at the formation of a superior personality by focusing on the process of maturing the quality of the logic of the heart, morals, and faith and the peak of life is the achievement of the perfection of the quality of life. The cause of the low quality of education in Indonesia is essentially the accumulation of causes of the low quality of education in schools. Many things that cause the low quality of education include Low-quality physical facilities, Low quality of teachers, Low teacher welfare, Lack of equal distribution of educational opportunities, Low relevance of education to needs, High cost of education. Models and strategies to improve the quality or quality of education at the elementary and secondary level with a strategy that emphasizes results (the output-oriented strategy), strategies that emphasize the process (the process-oriented strategy), and a comprehensive strategy (the comprehensive strategy)